Propuesta de mejora en el área de compras de una empresa manufacturera de mobiliario de madera - Palomino Arana, Danitza (2016)
This thesis presents a proposal to improve the shopping area of a manufacturing company of wooden furniture. The hypothesis states that by using quantitative forecasts of raw materials, inventory management, supplier management, development of operating procedures, formats and indicators were achieved to decrease the failure to date of delivery of final products manufactured by the company under study. The thesis is divided into six chapters. The first chapter deals with the analysis of the sector and the theoretical framework supporting in the research. The second includes analysis and diagnosis of the situation of the company. In the third chapter the proposed improvement is developed to solve the problem of non-delivery on the date identified in chapter two. The fourth chapter contains the validation of the proposal by using a simulator and contrasted with the actual recorded demand. The fifth chapter deals with the analysis of the impacts of the proposed improvements and the prevention and/or mitigation measures that are considered in the case of the negative impacts. Finally, in the sixth chapter; there are conclusions and recommendations on the implementation of the various tools listed.